Canone biblico e teologia biblica. Un rapporto necessario… difficile - Segalla, G. (Liber Annuus, 2006)
Abstract Biblical Canon and Biblical Theology are two realities tied together similar to the problem of a unique canon made of two Testaments in tension, and answer, to demonstrate the unity of the Scriptures. Having introduced the problem, two crucial moments are taken into consideration in which the canon has been at the center of theological reflection: the 70 with the German hermeneutics on the one hand and the American canonical critics on the other; the 90 with the proposal of three important “ Biblical Theologies”, examined for the answer they give to the problem of the canon. In last part the results are synthesized and an attempt is made to find a new way in order to demonstrate the unity of the Scriptures: the collective memory of Jhwh as the one God who has created the world and has chosen Israel and the memory of Jesus containing the former and bringing it to fulfillment in the definitive revelation of the God who saves all men.